STRATEGIES FOR MANAGEMENT THE TAIKIAM COMMUNITY MARKET UNDER NEW NORMAL, LAMAE SUBDISTRICT, LAMAE DISTRICT, CHUMPHON PROVINCE - Kaewpech , Kewwadee (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were: 1) study the context and management processes within the Tai Kiam Community Market under the new way of life, and 2) study the strategies for the management of the Tai Kiam Community Market under the new normal. The study was qualitative research by analyzing data from the document, in-depth interview tool and focus group discussion by choosing a specific sample. Key informants such as 1) Marketing Committee, and 2) Marketing Working Group, total 25 people. By content analysis and summary overview. The research was found that: 1. Tai Kiam Community Market Context The former area was an abandoned cemetery. There is a need for useful space to create a market. which is overseen by the market committee, has rules and has an average income of 700,000 baht / week, and management process It is a market for a self-reliant community. Encourage villagers to participate in the operation the market committee and working group are the leaders in the area. There is a concrete marketing plan and good management. And 2. Strategies for the management of the Tai Kiam Community Market consists of vision, mission, goals and strategies as follows: 2.1) Promote and develop online marketing. Create learning resources/conserve wisdom and raise product standards, 2.2) Develop the potential to connect to the community-based tourism network Create guidelines and methods for dealing with natural disasters and create measures to prevent the spread of COVID-19, 2.3) Develop activities to promote and build technology knowledge with merchants/vendors/ committees to build a relationship and study the needs of consumers for products, and 2.4) promote the distribution of products to have variety and maintain identity Create a service channel, Online advice and create an Online marketing development advice and create an online market to distribute products.